ONLINE LEARNING AND ENGLISH LANGUAGE DEVELOPMENT - Ergasheva Dilfuzaxon Tolibjon qizi,; Mannabova Ozoda Ilxom qizi,; Choriyeva Xurshidabonu Komil qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The  integration  of  digital  technologies  into  education  has  transformed  the process of language learning. Online learning has become one of the most effective approaches to English language development by providing learners with flexible access to  educational  resources,  communication  opportunities,  and  interactive  learning environments. This article examines the role of online learning in developing English language skills,  including  listening,  speaking, reading, and  writing. Furthermore,  it discusses  the  advantages  and  challenges  of  online  education  and  explores  modern digital  tools  that  facilitate  language  acquisition.  The  study  concludes  that  online learning significantly contributes to English language development when supported by effective teaching strategies and learner motivation.